Breeding the total judgment in the light Contemporary knowledge methods (Journal of the College of Basic Education, 2023)
The sensory impulse of humanity and the witness to the civilizational development of nations is represented in education. As an activity based on detection, description, analysis and synthesis of all aspects of human life. And by looking To the renewal and development that surrounds today's world, if it doubles the human sense of the need to confront the challenge to the mechanical and technical development of all aspects of contemporary life; What is required of education, if any always proceeding in the context of this development to modify methods and methods in the light of new knowledge environmental, social and political changes. Educational philosophy, like general philosophy, seeks to